The new rights in the constitutional State: some clarifications starting from the interest theory - Zezza, Michele (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
The main aim of this article is to show that there is a possible theoretical foundation of new emerging rights found in the idea that the rights, conceived as moral demands with logical and axiological priority over derivatives or derivable duties, constitute the germinal nucleus of mutable groups subjective positions (“grounds of duties”). This line of thought may be considered consistent with the attempt to assign to all rights, in principle, the same theoretical dignity, even when they are not recognized by a certain legal order. Therefore, their assertion only makes sense from the standpoint of legal moral criticism. doi: https://doi.org/10.20318/universitas.2017.3559